2022
DOI: 10.1002/slct.202202919
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal CatalysedC‐SCross‐Coupling Reactions at Room Temperature.

Abstract: Transition metal catalysed formation of Csp2-S bond through cross-coupling reaction stands important and powerful tools in synthetic organic chemistry. The reaction constitutes an important strategy for the synthesis of thioethers that possess diverse biological activities in medicine and agriculture. Nonetheless, maintaining reaction temperature during Csp2-S crosscoupling reaction decides fate of desired product along with possibility of by-product and disulfides. The economy of process, safety and environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Based on the reactivity of CuMoO 4 and BaMoO 4 in C–S and C–N cross-coupling reactions and earlier DFT studies, 13,14 a tentative plausible mechanism is suggested (Scheme 6). From the control experiment, it is evident that the monometallic salts of copper and molybdenum independently or in situ are not effective for this cross-coupling reaction.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Based on the reactivity of CuMoO 4 and BaMoO 4 in C–S and C–N cross-coupling reactions and earlier DFT studies, 13,14 a tentative plausible mechanism is suggested (Scheme 6). From the control experiment, it is evident that the monometallic salts of copper and molybdenum independently or in situ are not effective for this cross-coupling reaction.…”
Section: Resultsmentioning
confidence: 97%
“…In initial screening experiments, iodobenzene 1a and phenol 2a were used as classical substrates to establish suitable reaction conditions (Table 1). In the first phase of the study, the classical conditions were assessed using 3 mol% of CuMoO 4 catalyst 14 in 1 mL of water solvent and 2 equiv. KOH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross‐coupling reactions are one of the effective, versatile and direct methods for constructing C−C bonds [1,2] . They have greatly promoted the development of organic chemistry and have been one of the most popular areas of organic chemistry with an indispensable and significance role for the synthesis of complex molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-coupling reactions are one of the effective, versatile and direct methods for constructing CÀ C bonds. [1,2] They have greatly promoted the development of organic chemistry and have been one of the most popular areas of organic chemistry with an indispensable and significance role for the synthesis of complex molecules. Among them, Pd-catalyzed Sonogashira-Hagihara and Mizoroki-Heck coupling reactions of aryl or vinyl halides with terminal alkynes or reactive olefins under alkaline conditions are important and commonly used reactions, and the coupling products have been widely used in pharmaceuticals, dyestuff, advanced materials, supramolecular chemistry, etc.…”
Section: Introductionmentioning
confidence: 99%